Deep-sea glass sponge fauna (Porifera, Hexactinellida) of the tropical central Atlantic seamounts: new species and diversity patterns - Domingos, Celso; Kersken, Daniel; Hendry, Katharine; Schuster, Astrid; Taylor, Michelle L.; Xavier, Joana R. (Zootaxa, 2026)
Glass sponges constitute an important component of benthic communities, forming structural habitats in the deep-sea. Currently, 146 species of hexactinellids are known to occur in the Atlantic Ocean, with the majority reported at higher latitudes in the North Atlantic. Without a comprehensive understanding of their biodiversity across the entire Atlantic, conservation programs aimed at protecting these important organisms are limited in their effectiveness. To fill-in this knowledge gap, our research focuses on the examination of the glass sponge fauna inhabiting several seamounts (Carter, Gramberg, Knipovich, Vayda) and the Vema fracture zone, all located in Areas Beyond National Jurisdiction across the tropical Atlantic. This study identified 19 glass sponge species from 15 genera and 6 families, using an integrative taxonomic approach. Of these, 13 species are new to science and are herein described and illustrated. Phylogenetic reconstructions of partial mtDNA (COI and 16S rDNA) and nuclear rDNA (28S) markers confirm our taxonomic identifications and support previous studies on the phylogenetic status of these families. In the present work, we increased the number of known species for the Atlantic from 146 to 159. Many of these new species are from rarely studied genera, such as Caulophacella, Tabachnickia, Heterorete, Lonchiphora and Scyphidium. The discovery of such a high number of new species highlights the limited exploration and research in the tropical Atlantic area, where the diversity of deep-sea organisms is yet to be unravelled. This relatively unexplored region contains a substantial diversity of deep-sea life that remains to be fully studied and understood. The discovery of these new species not only enhances our understanding of biodiversity in this region but also provides crucial insights into broad distribution patterns, which is vital for developing new policies to protect these critical habitats.